2007
DOI: 10.4161/cc.6.22.4895
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of c-Myc by Ribosomal Protein L11

Abstract: Several ribosomal proteins including L11 have been shown to activate p53 by inhibiting oncoprotein MDM2, leading to inhibition of cell cycle progression. Our recent study showed that L11 also inhibits oncoprotein c-Myc. Overexpression of L11 inhibits c-Myc-induced transcription and cell proliferation, while reduction of endogenous L11 increases these c-Myc activities. Interestingly, L11 is a transcriptional target of c-Myc, thus forming a negative feedback loop. We further showed that L11 competes with co-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 89 publications
2
60
0
Order By: Relevance
“…Subsequently, increased rpL11 will be also involved in the p53 activation and negatively regulate the level of c-myc. This supposition is the same as the previous report, which RPL11 acts as a feedback regulator of c-Myc (Dai et al, 2007). In Figure 4d, rpL11 knockdown partly decreased the p53 level in the aberrant ribosome biogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, increased rpL11 will be also involved in the p53 activation and negatively regulate the level of c-myc. This supposition is the same as the previous report, which RPL11 acts as a feedback regulator of c-Myc (Dai et al, 2007). In Figure 4d, rpL11 knockdown partly decreased the p53 level in the aberrant ribosome biogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…However, it remains intriguing to explore their extra-ribosomal functions in the p53-indepentent pathway. RPL11 was recently found to not only inhibit c-Myc transcriptional activity by directly binding to its MBII domain (37,47), but also suppress c-Myc mRNA expression via a miRNA-mediated mechanism (38). It remains possible that RPL11 might not be the only ribosomal protein that regulates c-Myc activity and stability, given that nearly a dozen of ribosomal proteins, including RPL11, RPL5 RPL23, RPS7, and RPS14, have been shown to play a role in regulation of the MDM2-p53 pathway (48 -55).…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that L11 regulates c-Myc levels (12,15). However, the underlying mechanism is not clear.…”
mentioning
confidence: 87%
“…Knockdown of L11 drastically increased the levels of c-Myc protein (12) (bottom panels of Fig. 1A) and c-myc mRNA (15) in U2OS cells. RT-qPCR assays revealed that the levels of c-myc mRNA were markedly increased upon knockdown of L11 (top panel of Fig.…”
Section: L11mentioning
confidence: 99%